2014
DOI: 10.1007/s00441-014-1878-9
|View full text |Cite
|
Sign up to set email alerts
|

Circadian oscillators in the mouse brain: molecular clock components in the neocortex and cerebellar cortex

Abstract: The circadian timekeeper of the mammalian brain resides in the suprachiasmatic nucleus of the hypothalamus (SCN), and is characterized by rhythmic expression of a set of clock genes with specific 24-h daily profiles. An increasing amount of data suggests that additional circadian oscillators residing outside the SCN have the capacity to generate peripheral circadian rhythms. We have recently shown the presence of SCN-controlled oscillators in the neocortex and cerebellum of the rat. The function of these perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…Genes that regulate the rhythmicity of neurons in the SCN are called clock genes. Several clock genes, including Arntl, Nr1d1, Bmal1, Per1, Per2, and Cry1, have also been found in the Purkinje cell and granular cell layer of the cerebellum [132,133]. Their expression pattern follows that of the SCN, but with a delay of 5 h [132,134].…”
Section: Clock and Wake-sleep-related Genes In The Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…Genes that regulate the rhythmicity of neurons in the SCN are called clock genes. Several clock genes, including Arntl, Nr1d1, Bmal1, Per1, Per2, and Cry1, have also been found in the Purkinje cell and granular cell layer of the cerebellum [132,133]. Their expression pattern follows that of the SCN, but with a delay of 5 h [132,134].…”
Section: Clock and Wake-sleep-related Genes In The Cerebellummentioning
confidence: 99%
“…Several clock genes, including Arntl, Nr1d1, Bmal1, Per1, Per2, and Cry1, have also been found in the Purkinje cell and granular cell layer of the cerebellum [132,133]. Their expression pattern follows that of the SCN, but with a delay of 5 h [132,134]. Even in vitro the cerebellum is able to express near-24-h rhythms and these rhythms can be shifted by shifting 'mealtime' exposure [135].…”
Section: Clock and Wake-sleep-related Genes In The Cerebellummentioning
confidence: 99%
“…In contrast to a much longer (24 h) circadian rhythm, which relies on the rhythmic expression of a set of clock genes with specific daily profiles in the suprachiasmatic nucleus and other parts of the brain (Rath et al, 2014), the interval timing in the sub-to supra-second range mainly relies on neuronal mechanisms. To understand the mechanisms underlying the neuronal clocks, one should first look at the mechanisms of the mechanical and electronic clocks.…”
Section: Introductionmentioning
confidence: 99%
“…Whether light has a direct effect on its expression in the cerebellum has not yet been clarified. It has also been shown that the cerebellum is involved in maintaining the circadian rhythm in rodents through clock gene regulation [53,54], and OPN4 resets the circadian clock through the activation of clock gene Per1 [55]. Therefore, we must consider the possibility that OPN4 may affect the circadian rhythm through clock gene activation in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%